On k-Ramsey Numbers of Stripes
For bipartite graphs F and H with Ramsey number R(F, H) = n and an integer k with 2 < k < n, the k-Ramsey number of F and H is the minimum order of a balanced complete k-partite graph G for which every red-blue coloring of G results in a subgraph of G isomorphic to F all of whose edges are colored red or a subgraph isomorphic to H all of whose edges are colored blue. In this work, we investigate the k-Ramsey numbers Rk(F